Hospital Provincial General Docente Riobamba NOTA EDITORIAL, VOLUMEN 8, REVISTA EUGENIO ESPEJO - Dra. Yaira María Barranco Ruiz Ph. D. (2017)
Informally, the practice of some techniques that are part of alternative medicine was know in Ecuador and Riobamba. Therefore, a study was done to find out and determine the level of acceptance that the practice of the alternative medicine has in the population of the urban area of the city of Riobamba, in the period January - March 2012 for that the collaboration of 40 students of the fifth year, parallel “B” of Medicine, promotion 2011-2012 was required, in a controlled manner the survey was carried out to 9,116 people in each of the urban parishes. The results show that people have certain levels of general knowledge about some techniques of alternative medicine, and a wide acceptance to put them in practice and also to have access to treatments, especially with acupuncture and homeopathy.